2018
DOI: 10.18311/jnr/2018/22249
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal KAP Study on HPV Immunised Adolescents’ in Malaysia

Abstract: HPV infection invades every sexually active human, at least once in their life time and young adults are especially at higher risk (50%) for Cervical Cancer (CC) in Asia Pacific region 1 . Though, more than 140 HPV types are identified, strong evidence has been observed for two high risk types-16 and 18 (>70-80% of all cases)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…A weak positive association (ϕ=0.068) was observed between faculty variable and response of the students. The results of present study regarding diagnosing of Ebola virus disease is similar to other studies according to them pharmacy students had more better knowledge about the disease [16][17].…”
Section: Discussionsupporting
confidence: 89%
“…A weak positive association (ϕ=0.068) was observed between faculty variable and response of the students. The results of present study regarding diagnosing of Ebola virus disease is similar to other studies according to them pharmacy students had more better knowledge about the disease [16][17].…”
Section: Discussionsupporting
confidence: 89%
“…The 15 studies were conducted in a diverse range of countries including 3 from the US 22,50,51 , 2 from Sweden 3,52 , 2 from Nigeria 53,54 , 1 from Germany 55 , 1 from Hungary 38 , 1 from Australia 8 and 1 from the UK 56 . The remaining 4 studies were from Asia including Singapore 57 , Taiwan 28 , Hong Kong 37 and Malaysia 58 . Study sizes ranged considerably with the largest being Davies et al's 8 study which included 6,965 students while Yoost et al 51 conducted a study with only 21 students completing all aspects of the study.…”
Section: Population Profilesmentioning
confidence: 99%
“…Post-intervention, all fifteen studies reported a statistically significant improvement in their specific outcome measures including changes in knowledge, attitude and perception with regard to HPV vaccination and associated cancer prevention. All of the studies aimed to improve knowledge related to HPV risk and HPV vaccination while many focused on improving positive attitudes/perceptions regarding self-protection against acquirement of HPV 3,8,22,28,37,38,51,52,57,58 . Only 3 of the fifteen studies explored the actual effect of the intervention on HPV vaccination uptake 3,8,51 .…”
Section: Outcome Measures Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations